Stage 1 Hypertension in Nulliparous Pregnant Patients and Risk of Unplanned Cesarean Delivery - Natenzon, Anna; Parrott, Caitlin W.; Manem, Nihita; Zelig, Craig M. (American Journal of Perinatology, 2022)
Objective The aim of the study is to determine whether stage 1 hypertension is a risk factor for cesarean at ≥390/7 weeks.Study Design This is a retrospective cohort study of nulliparas delivering at ≥390/7weeks. Exposure was defined as stage 1 hypertension and compared with normotension. The primary outcome was unplanned cesarean. Statistical analysis was performed using SPSS 27.Results Two hundred and fifty patients had stage 1 hypertension and 250 had normotension. Thirty-eight percent of the patients with stage 1 hypertension required cesarean as did 22% of controls (risk ratio [RR]=1.55, 95% confidence interval [CI]: 1.23–1.96, p <0.001). This remained significant after controlling for confounders in a logistic regression (odds ratio [OR]=1.61, 95% confidence interval [CI]: 1.02–2.55, p <0.040). Upon secondary analysis, these results were statistically significant for gestational age ≥395/7 weeks (adjusted odds ratio [AOR]=1.89, 95% CI: 1.05–3.39, p=0.033) but not from 390/7 to 394/7weeks (AOR=0.68, 95% CI: 0.31–1.50, p=0.34).Conclusion In nulliparas, stage 1 hypertension is an independent risk factor for unplanned cesarean.Key Points
Keywords: cesarean delivery; hypertension; placental insufficiency